PROSES PERUMUSAN KEBIJAKAN PENYERTAAN MODAL PEMERINTAH KOTA YOGYAKARTA PADA PERUSAHAAN DAERAH JOGJATAMA VISHESHA TAHUN 2012 - , NINDA MUSLIHAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
LocalâOwned Enterprise is a governmentâowned business unit that aims to optimize the economic potential in the region in an effort to explore and develop local resources, provide public services or public services as well as forâprofit or profit motive. With the local regulation of provincial enterprise, then the next executive in this case Yogyakarta City Government submitted a draft local regulations on capital investment as a condition to be able to run this enterprise. After that, the executive with the legislative level discuss the draft regulations. If the draft is agreed, it will be legislated and the city will has a local government enterprise with name of Jogjatama Vishesha local company that will manage The XT Square. XT Square is a former bus station building that has been completed since 2010 . The long time of decision making process of Yogyakarta Cityâs asset transfer to local government enterprise, made the XT Square building was unâused until 2012. The existence of issues surrounding the equity process and the presence of the attractive interest between diverse actors. It is the goal of this research is to determine how the policyâmaking process and the factors that influence the capital investment in PD Jogjatama Vishesha which the discussion conducted by the executive together with the the legislative. Policy analysis perspective is used politically, to try to combine several theories of public policy. Contestation and interaction in the formulation of capital investment using a qualitative descriptive approach with historical exploratory method, as it aims to provide a holistic sense of the phenomenon of the cases that have occurred in the past. In the process of data collection was conducted through inâdepth interviews and literature study to document the planning process of equity owned by the municipal government of Yogyakarta during the formulation process to the decisionâmaking capital investments on October 1, 2012. It becomes limiting the discussion in this study. Capital investment policy formulation process can be devided into twoâstage process, which is a process that occurs technocratic and politically. In the technocratic process capital investment by the executive lawâabiding orientation is technical and public policy on capital investment. While the presence of political factors on the part of legislative that the interest among parliament, fears of loss of assets and also chairman of the commission C which is actually responsible for the asset discussion ran for mayor of Yogyakarta. Due to the slow pace of the approval of Parliament led to cost incurred for the City Government of electricity, water and maintenance costs as well as other operational XT Square continues to increase and is a burden on the City of Yogyakarta.Â The next expected election of directors is determined by the competent and free from political influence parties concerned. It also should understand what the community needs and can immediately take the deal in favor of the interests of local and regional community to the next company really should be sought for professionally managed to be independent and